2015
DOI: 10.1007/s00436-015-4489-9
|View full text |Cite
|
Sign up to set email alerts
|

Oxime derivatives with larvicidal activity against Aedes aegypti L.

Abstract: Oximes containing secondary metabolites constitute an important group of bioactive compounds and have been described and frequently updated in the literature due to their pharmacological properties. Thus, the aim of this study was to evaluate the larvicidal activity of a series of fourteen structurally related [1,4]-Benzoquinone mono-oximes on third-instar Aedes aegypti larvae and to investigate structure-activity relationships (SAR) of these compounds. Results of larvicidal assay revealed that all oximes were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 30 publications
3
5
0
Order By: Relevance
“…Alteration in the structure of indole and tryptamine resulted in modulation in formicidal activity. Similar results were found, in which synthetic modification of oxime, eugenol, tryptamine, monoterpenes, sulfilimines and amino acid resulted in modulation in insecticidal/larvicidal activities (Barbosa et al, 2012;Lima et al, 2015;Nguyen, Chompoo, & Tawata, 2015;Oliveira et al, 2014;Santos et al, 2011;Zhou et al, 2014).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Alteration in the structure of indole and tryptamine resulted in modulation in formicidal activity. Similar results were found, in which synthetic modification of oxime, eugenol, tryptamine, monoterpenes, sulfilimines and amino acid resulted in modulation in insecticidal/larvicidal activities (Barbosa et al, 2012;Lima et al, 2015;Nguyen, Chompoo, & Tawata, 2015;Oliveira et al, 2014;Santos et al, 2011;Zhou et al, 2014).…”
Section: Discussionsupporting
confidence: 84%
“…The discovery of new compounds by synthetic derivation has been successful in the management of important pest insects (Alvarenga et al., ; Lima et al., ; Sun & Zhou, ; Yang, Li, Wu, Liu, & Chang, ) demonstrating that the variation of chemical radicals in the structure of the compound may be responsible for differences observed in their activities. This relationship between structure and activity may indicate compounds more favourable to biological action and help in the optimization of insecticides by including, for example, characteristics that have a low environmental impact.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we demonstrated the specificity of the larvi- 158.98 to 69.94 μg/ml) (Bharathi et al, 2014), benzoquinone monooximes (LC50 = 9.86 μg/ml) (Lima et al, 2015), R-and S-limonene (LC50 = 27 and 30 μg/ml, respectively) (Santos et al, 2011) and tryptamine (LC50 = 48 μg/ml) (Oliveira et al, 2014). In contrast, N-substituted methyl maleamates exert strong larvicidal effect against A. aegypti (LC50 = 0.36 μg/ml) at 24 hr of treatment (Harburguer et al, 2018).…”
Section: Discussionsupporting
confidence: 60%
“…Other compounds are less efficient in killing Ae. aegypti larvae after 24 hr of exposure, such as eugenol derivatives (LC50 values ranging from 67 to 113 μg/ml) (Barbosa et al, ), dihydrophenanthroline‐3‐carbonitriles (LC50 values ranging from 158.98 to 69.94 μg/ml) (Bharathi et al, ), benzoquinone mono‐oximes (LC50 = 9.86 μg/ml) (Lima et al, ), R‐ and S‐ limonene (LC50 = 27 and 30 μg/ml, respectively) (Santos et al, ) and tryptamine (LC50 = 48 μg/ml) (Oliveira et al, ). In contrast, N‐ substituted methyl maleamates exert strong larvicidal effect against A. aegypti (LC50 = 0.36 μg/ml) at 24 hr of treatment (Harburguer et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation